2023
DOI: 10.1038/s41593-023-01257-z
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular cells induce microglial phagocytic states and synaptic engulfment via SPP1 in mouse models of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is characterized by synaptic loss, which can result from dysfunctional microglial phagocytosis and complement activation. However, what signals drive aberrant microglia-mediated engulfment of synapses in AD is unclear. Here we report that secreted phosphoprotein 1 (SPP1/osteopontin) is upregulated predominantly by perivascular macrophages and, to a lesser extent, by perivascular fibroblasts. Perivascular SPP1 is required for microglia to engulf synapses and upregulate phagocytic marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 87 publications
0
72
0
Order By: Relevance
“…Complement-dependent engulfment has frequently been implicated in excessive synaptic elimination leading to functional deficits 37, 38, 40 . In the CNS, α-syn is known to be enriched at presynapses 48 , but the subcellular localization of α-syn within enteric neurons is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement-dependent engulfment has frequently been implicated in excessive synaptic elimination leading to functional deficits 37, 38, 40 . In the CNS, α-syn is known to be enriched at presynapses 48 , but the subcellular localization of α-syn within enteric neurons is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we found that enteric α-syn preferentially localizes to the pre-synaptic space. Moreover, although excessive synaptic pruning due to α-syn has not been shown, it is a well-studied mechanism for cognitive dysfunction in Alzheimer’s-related pathology 37, 38, 70 . Additionally, ENS macrophages engage in synaptic refinement during development 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Spp1 is increased in microglia from mouse models of AD (18, 50) and a marker of the DAM/ARM/MGnD phenotype. Recently, perivascular macrophage expression of Spp1 was shown to be necessary for microglial engulfment of synapses and upregulation of phagocytic markers in the mouse hippocampus with amyloid pathology (51). This finding suggests that higher expression of Spp1 in aged female microglia may lead to a greater susceptibility to neurodegeneration in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the quantifiable neuropathology of β-amyloid plaques (Aβ) and neurofibrillary tangles (NFTs) 6 , the exact neurobiological mechanisms underlying Alzheimer's disease (AD) remain elusive. Brain myeloid-origin immune cells, including microglia and perivascular macrophages (PVMs), play crucial roles in the pathogenesis of AD [1][2][3][4][7][8][9][10] , providing neuroprotective benefits by clearing lesions, but also exacerbating the disease through the induction of excessive neuroinflammation 11 . While previous studies utilizing single-nucleus/-cell RNA sequencing (snRNA-seq/scRNA-seq) have made significant progress describing complex functional roles of murine and human microglia in AD 4,[12][13][14][15] , challenges with characterizing the wide spectrum of microglial heterogeneity and identifying more nuanced AD-associated subtypes still remain, largely due to limited sample sizes and differences in the single-cell technologies used.…”
Section: Mainmentioning
confidence: 99%
“…
Microglia and perivascular macrophages, myeloid-origin resident immune cells in the human brain, play crucial roles in Alzheimer's disease (AD) [1][2][3][4] . However, the field lacks a unified taxonomy describing their heterogeneity and plasticity 5 .
…”
mentioning
confidence: 99%